A Linguistic Landscape in Purwokerto: Power and Solidarity Stand Strong in a Culinary Center - Pamuji, Eko; Khristianto, Khristianto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
This paper is about the existence of linguistics landscape along the Soeharso’s street Purwokerto which shows the diverse people in using language of their stores, restaurants, eateries, cafes, or street vendor banner whereby traders use their own prominent language in monolingualism, bilingualism, or multilingualism. For restaurants, eateries, or street vendors, they include person’s name as their stall name, and also include the origin of the food pioneer to show their sense of solidarity, while shops, distros, cafes include English as a powerful weapon in attracting customers based on prestige. Both phenomenon are evidence of how the power and sense of solidarity are raised into the name of business places they build as their strategy in marketing and introducing their business.